2022
DOI: 10.53576/bashir.003.01.0053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sustained natural apophyseal glides combined with transcutaneous electrical nerve stimulation in cervical radiculopathy

Abstract: To analyze the effects of Sustained Natural Apophyseal Glides (SNAGs) combined with Transcutaneous Electrical Nerve Stimulation (TENS) in Cervical Radiculopathy. Quasi experimental study design was selected. Samples of 20 male and female participants diagnosed with cervical radiculopathy were assigned to receive SNAGs combined with TENS.  Age of population between 35 to 55 years. The duration of intervention was 4 weeks, at 4 sessions per week. The Visual Analogue Scale (VAS) for pain and Goniometer for cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…2 These include stenosis of the intervertebral foramen due to compression, irritation, traction, and a lesion on the nerve root brought on by a herniated disc, foraminal narrowing, or degenerative spondylotic alteration. 3 Cervical radiculopathy is usually the primary clinical symptom following injury or compression to a nerve root in the cervical spine and causing uneasiness. 4 Parkinson originally characterized the condition in 1817 Although he concluded that it was a rheumatic disease of the deltoid muscle.…”
Section: Introductionmentioning
confidence: 99%
“…2 These include stenosis of the intervertebral foramen due to compression, irritation, traction, and a lesion on the nerve root brought on by a herniated disc, foraminal narrowing, or degenerative spondylotic alteration. 3 Cervical radiculopathy is usually the primary clinical symptom following injury or compression to a nerve root in the cervical spine and causing uneasiness. 4 Parkinson originally characterized the condition in 1817 Although he concluded that it was a rheumatic disease of the deltoid muscle.…”
Section: Introductionmentioning
confidence: 99%